Implementing SOP to Improve Butler Performance - Ni Made Wulan Dwi Artini; I Ketut Suarja; I Gde Agus Jaya Sadguna; Ni Made Sudarmini (International Journal of Glocal Tourism, 2020)
Purpose: The research is to determine whether the implementation of standard operating procedure (SOP) can improve the performance of a butler in a hotel located in Jimbaran tourist area, Bali, Indonesia, and find out the efforts that can be applied to improve the performance of the butler employees. Research methods: This research uses descriptive qualitative method using data collection methods such as observation method by directly observing how a hotel butler handles guests. An interview is done to butler employees, head butler and room division manager; and finally using questionnaires given to all butlers. Findings: All butler of the hotel executes the SOP accordingly and correctly and have also worked optimally. The implementation of the SOP that are well implemented by butler employee has a positive impact on employee performance thus they can work thoroughly, disciplined, and in an organized manner. Implication: SOP is very important to be implemented by butler to improve the performance of butler employees at the hotel.